2018
DOI: 10.1007/s10620-018-5394-8
|View full text |Cite
|
Sign up to set email alerts
|

Significant Morbidity and Mortality Associated with Fecal Impaction in Patients Who Present to the Emergency Department

Abstract: Background: Fecal impaction (FI) is defined by a large mass of stool in the rectum and/or colon that is unable to be evacuated. No literature to date details demographics and outcomes in a sizeable sample of FI patients in the United States. Aims: The present study aims to develop knowledge of FI by reporting descriptive measures and outcomes of patients presenting to a U.S. emergency department (ED) with FI. Methods: Medical charts coded with FI at Beth Israel Deaconess Medical Center from 2016 or 2017 were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…We postulate that stercoral colitis may result in micro-perforation and accumulation of gas and hence manifests as pneumoperitoneum. It is crucial to diagnose and address stercoral colitis and prevent bowel perforation [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that stercoral colitis may result in micro-perforation and accumulation of gas and hence manifests as pneumoperitoneum. It is crucial to diagnose and address stercoral colitis and prevent bowel perforation [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…2 One retrospective article of patients who presented with fecal impaction at Beth Israel Deaconess Medical Center reported that at least 54.8% of these patients were taking at least one commonly prescribed constipation causing medication. 3 In another retrospective study of 130 patients who presented to a tertiary center in Beirut with fecal impaction reported 75.3% had at least one of the following concurrent conditions: heart disease, neurological disease, diabetes, or being bedridden. In over two-thirds of these patients, the site of impaction was the rectum.…”
Section: Introductionmentioning
confidence: 99%
“…Fecaloma, a rare cause of fecal impaction, is an accumulation of hardened impacted stool typically occurring in the sigmoid colon and rectum and affecting, especially, elderly patients. [1][2][3][4][5] Symptoms of fecaloma are non-specific, dominated by constipation, abdominal pain, abdominal distention, nausea and vomiting. [3][4][5] The diagnosis is made through abdominal computed tomography scan (CT scan), X-rays or abdominal ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Symptoms of fecaloma are non-specific, dominated by constipation, abdominal pain, abdominal distention, nausea and vomiting. [3][4][5] The diagnosis is made through abdominal computed tomography scan (CT scan), X-rays or abdominal ultrasound. 1,2 Fecaloma is often managed conservatively by manual disimpaction, laxatives and enemas.…”
Section: Introductionmentioning
confidence: 99%